Analisis Pola Asuh Anak Dari Dampak Lingkungan Terhadap Keterampilang Berhitung Siswa - Jaelani Pikri; Donna Boedi Maritasari; Rifaatul Mahmudah (Lembaga Bale Literasi, 2022)
This study discussed the Analysis of Child Parenting Patterns from Environmental Impacts on Students' Counting Skills at SD Negeri 1 Sunanggalih. This study aimed to determine the form of parenting and the impact of the school environment on numeracy skills. The resource persons in this study consisted of 22 people in the form of 10 parents, 10 students and 2 teachers. This research was a qualitative research with data collection methods using the instruments of observation, interviews, and documentation. The data analysis technique was used the following steps: data reduction, data presentation, and conclusion drawing. The results showed that there were two forms of parenting applied by parents, namely democratic parenting and permissive parenting. The school environment had a great influence on students' numeracy skills